Distribution of the Invasive Diatom Didymosphenia Geminata (Bacillariophyceae) in Patagonian Water Bodies of Argentina - Lamaro, Anabel Alejandra (2019)
Background and aims: Didymosphenia geminata is a freshwater diatom that forms dense soggy carpet-like layers lining the bottom of aquatic environments. In Argentina the Secretaria de Ambiente y Desarrollo Sustentable de la Nacion declared it exotic invader species. In the lasts 9 years it has colonized rivers from Patagonia and its distribution in the region has considerably widen. The aim of this paper is to analyze the dynamic of this species invasion in Argentinean Patagonia through the use of Geographic Information Systems (GIS). M&M: the analyzed data were obtained by our team in Neuquen and Chubut provinces and also from technical reports published by universities or governmental institutions in websites. A database at regional scale from Neuquen to Tierra del Fuego was built considering presence-absence data, geographic position and dates and in some cases environmental data (pH, conductivity, etc.) Results: the results were incorporated to a GIS using Q-Gis 2.14 an open source and free software that allowed us to generate distribution maps at national and provincial level. Conclusions: the available data show that D. geminata has widen its distribution since 2010 to present from Chubut province to the north reaching Neuquen province and to the south up to Tierra del Fuego province.